Dimensionamento e custo do capital de giro em uma corporação com atividades diversificadas - Koppe, Sidney Augusto (Universidade do Vale do Rio dos Sinos, 2014)
This case study is aimed at presenting a methodology for dimensioning and calculating the cost and Working Capital of a diversified Corporation with a single account, using as a base the background of two-year-management-financial statements (2012 and 2013). As of the tabulation of this background information, this study presents the Working Capital of each Business Unit which comprises the Corporation, by showing the composition of working assets and liabilities, the vertical analysis of the composition of working capital and the financing sources of working capital, which are spontaneous or onerous sources (Debt Capital and Equity). In order to assist data analysis and interpretation, the study uses statistical calculations for measures of dispersion and correlation among the accounts which comprise the Working Capital. Based on this information, the need of Working Capital, the Financial Cycle, the Cost of Financing Working Capital for each Business Unit and its weighted average cost are presented. Finally, this study presents the main results seen in the analysis, the correlations existing in the composition of Working Capital and suggests maximum and minimum necessity level of Working Capital for each Business Unit.
Keywords: Capital de giro; Necessidade de capital de giro; Custo do capital de giro; Dimensionamento do capital de giro; Working capital; The need of working capital; The cost of working capital; Dimensions of working capital